Chromatic Dispersion Manipulation Based on Metalenses. Issue 27 (11th December 2019) - Zang, Wenbo; Yuan, Quan; Chen, Run; Li, Lin; Li, Tianyue; Zou, Xiujuan; Zheng, Gaige; Chen, Zhuo; Wang, Shuming; Wang, Zhenlin; Zhu, Shining
Abstract: Metasurfaces are 2D metamaterials composed of subwavelength nanoantennas according to specific design. They have been utilized to precisely manipulate various parameters of light fields, such as phase, polarization, amplitude, etc., showing promising functionalities. Among all meta‐devices, the metalens can be considered as the most basic and important application, given its significant advantage in integration and miniaturization compared with traditional lenses. However, the resonant dispersion of each nanoantenna in a metalens and the intrinsic chromatic dispersion of planar devices and optical materials result in a large chromatic aberration in metalenses that severely reduces the quality of their focusing and imaging. Consequently, how to effectively suppress or manipulate the chromatic aberration of metalenses has attracted worldwide attention in the last few years, leading to variety of excellent achievements promoting the development of this field. Herein, recent progress in chromatic dispersion control based on metalenses is reviewed. Abstract : The metalens is one of the most basic and important applications of metasurfaces. The noticeable achievements over the past few years in the field of chromatic dispersion control based on metalenses are highlighted, especially in the development of achromatic metalenses. A perspective on this specific branch of applications and future prospects are also presented.